Indirect effect of Covid-19 on Vegetation Indices around the cement plant of Gabes region - Ben Atia, Zrouga Khaoula; Ben Amor, Afef; Dridi, Almohandes Bouthaina; Khebour Allouche, Faiza (جامعة الوادي - university of el oued, 2021)
To contain the Covid-19 pandemic, Tunisia imposed a national lockdown at the end of March 2020, a decision that resulted in a massive industrial complexes shutting down. The cement industry of Gabes was one of these complexes. However, to assess the impact of Covid-19 on the state of the vegetation around this industry three radiometric vegetation indices (RIs), NDVI, SAVI and EVI, were calculated from two Sentinel-2A imageries extracted at 22th December 2018 and 16th December 2020. Six plant species such as Oleo europaea, Ficus caria, Medicago sativa, Prunus persica vulgaris, Zygophyllumalbum and Helianthemum kahiricum were collected from 30 sites. Results suggest that, the period of pre-outbreak has the lowest averages of RIs. While, the after outbreak date has the higher levels of RIs presenting especially perennial species such as Oleo europaea. Then, EVI was the most higher index comparing to the rest of indices whatever the year studied. It was the most sensitive to cement dust and more susceptible to detect defoliation. Finally, through a remote application (RIs), the period of confinement allowed to improve the state of the vegetation surrounding the cement plant. It has helped the ecosystem to regenerate, especially perennial plant species.
Article
Keywords: Cement Plant; Plant Cover; Sentinel 2A; Covid-19; Radiometric Vegetation Indices.